2007
DOI: 10.1074/jbc.m700647200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Dihydroceramide Desaturase in Cell Cycle Progression in Human Neuroblastoma Cells

Abstract: The role of dihydroceramide desaturase as a key enzyme in the de-novo pathway of ceramide generation was investigated in human neuroblastoma cells (SMS-KCNR). A novel assay using water soluble analogs of dihydroceramide, dihydroceramidoids (D-e-dhCCPS analogs) was used to measure desaturase activity in-situ. Conversion of D-e-C12-dhCCPS (C12-dhCCPS) to its 4,5-desaturated counterpart: D-e-C12-CCPS (C12-CCPS) was determined by LC/MS analysis. The validity of the assay was confirmed by C8-cyclopropenylceramide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
167
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 43 publications
24
167
0
Order By: Relevance
“…1, a number of enzymes participate in the salvage pathway, and these include members of the LASS family, acid SMase, and acid ceramidase. The relatively recent development of RNAi [66] has allowed the selective knock-down of these genes individually [23,[67][68][69][70]. The implication of several of the above genes along the pathway of ceramide formation provides strong evidence for the operation of this pathway.…”
Section: Iii) An Increase In Free Sphingosinementioning
confidence: 99%
“…1, a number of enzymes participate in the salvage pathway, and these include members of the LASS family, acid SMase, and acid ceramidase. The relatively recent development of RNAi [66] has allowed the selective knock-down of these genes individually [23,[67][68][69][70]. The implication of several of the above genes along the pathway of ceramide formation provides strong evidence for the operation of this pathway.…”
Section: Iii) An Increase In Free Sphingosinementioning
confidence: 99%
“…It has also been shown that the combined use of lactoferricin and tamoxifen, due to its known inhibitory effect on GCS function, enhances the apoptotic effects of lactoferricin, and thus, it leads to increased levels of apoptosis in Jurkat T cell leukemia cells [79]. The imino sugar OGT2378 that is also an inhibitor of GCS reduced the tumorigenic capability of MEB4 melanoma cells [80]. It has been shown that GCS is overexpressed in many multidrug-resistant cancer cell lines in leukemia, breast cancer, and renal cell cancer [64].…”
Section: Glucosylceramide Synthase In Cancer Therapymentioning
confidence: 99%
“…HPR-induced production of ceramide mainly occurs via de novo synthesis, because HPR activates both serine palmitoyltransferase and dihydroceramide synthase (20,21) that catalyze the first steps in sphingolipid biosynthesis (22). Moreover, it has been recently shown that HPR concomitantly inhibits dihydroceramide desaturase (22,23), suggesting that dihydroceramide rather than (or in addition to) ceramide might mediate HPRinduced toxicity (24) possibly involving other mechanisms of death in addition to apoptosis. In this work, we investigate whether the resistance to HPR of human ovarian cancer cells could be associated with the activation of the SK/S1P leading to an altered dihydroceramide/S1P ratio that could prevent or overcome ceramide-mediated HPR-induced cell death.…”
mentioning
confidence: 99%